THU0409 Not just a swollen big toe: increasing all-cause hospitalizations in patients with gout in the united states: 1993–2014. (15th June 2017) - Singh, G; Mithal, A; Mithal, A
Abstract : Background: Gout is a disorder of uric acid metabolism and often presents as acute severe joint pain. However, several recent studies have highlighted systemic complications of associated hyperuricemia in patients with gout, including possible increased risk of renal and cardiovascular comorbidities. Objectives: To study all-cause hospitalizations in patients with gout in the United States (US) from 1993 to 2014. Methods: The Nationwide Inpatient Sample (NIS) is a stratified random sample of all US community hospitals. It is the only US national hospital database with information on all patients, regardless of payer, including persons covered by Medicare, Medicaid, private insurance, and the uninsured. We examined all inpatient hospitalizations in NIS from 1993 to 2014 with a primary or secondary diagnosis of gout, and compared them to total all-cause US hospitalizations during the same period. US population estimates and projections for the resident US population were obtained from the US Census Bureau. Results: There were 789.8 million all-cause hospitalizations in 6.4 billion person-years of observation from 1993 to 2014 (123.4 hospitalizations per 1, 000 person-years). During this time-period, 9, 741, 598 hospitalizations occurred in patients with gout (152.2 per 100, 000 person-years). All-cause US hospitalizations increased from 33.7 million in 1993 to 35.4 million in 2014, an increase of 4.8% over 22 years (Figure, dotted blue line). All-cause hospitalizations in gout patients have increased from 167, 441 in 1993 (64.2 per 100, 000 person-year) to 854, 475 in 2014 (267.9 per 100, 000 person-years, a dramatic increase of over 410% (p<0.0001, Figure solid red line). In 2014, hospitalizations in gout patients accounted for over 4.6 million hospital days at a total national cost of over US $42.6 billion. Conclusions: All-cause hospitalizations in patients with gout in the US have significantly increased by 410% in the last 22 years, almost hundred-fold of the 4.8% increase in US population all-cause hospitalization rate in the same time-period. This calls for an increase need for identification and management of serious co-morbid conditions in patients with gout. Disclosure of Interest: G. Singh Grant/research support from: Horizon Pharmaceuticals, A. Mithal: None declared, A. Mithal: None declared